The Peran Inflamasi Pepsin dan IL-8 pada Otitis Media Supuratif Kronis Aktif dengan Refluks Laringofaringeal: Studi Cross-Sectional - Danni Mahendra; Pratiwi Dewi; Hadi Sudrajad (Oto Rhino Laryngologica Indonesiana, 2026)
Background: Chronic suppurative otitis media (CSOM) is a chronic inflammatory condition of the middle ear, characterized by tympanic membrane perforation and persistent or recurrent ear discharge. The active phase of CSOM refers to a period of ongoing intense inflammation, marked by purulent exudate production, active infection, and heightened immune response. One of the contributing factors in CSOM pathogenesis is laryngopharyngeal reflux (LPR). Studies suggest that refluxed pepsin from LPR can reach the middle ear through the Eustachian tube, triggering local inflammation and exacerbating tissue damage during the active phase. Pepsin plays a role in upregulating pro-inflammatory cytokines, such as interleukin-8 (IL-8), thereby intensifying the inflammatory response and worsening CSOM symptoms in this stage. Purpose: To determine the correlation between pepsin and IL-8 levels in middle ear secretions of patients with active CSOM and LPR. Method: This cross-sectional study involved 32 patients with active CSOM and clinical signs of LPR. Middle ear secretions were analyzed for pepsin and IL-8 concentrations using enzyme-linked immunosorbent assay (ELISA). Pearson correlation was used to assess the relationship. Result: The study population was predominantly aged 36-45 years (28.12%) and female (59.4%). The mean pepsin concentration in middle ear secretions was 71.52±84.64 ng/mL, while the mean IL-8 level was 33.47±17.56 pg/mL. A strong and statistically significant positive correlation was observed between pepsin and IL-8 levels (r = 0.682; p = 0.001). Conclusion: Elevated pepsin levels due to LPR, strongly correlate with increased IL-8 expression, suggesting a reflux-mediated inflammatory mechanism in the pathogenesis of active CSOM.